Analisis Kesesuaian Penerapan Prinsip Efektif dan Efisien Pengadaan Barang dan Jasa Konstruksi Pemerintah di Surabaya: Analisis Kesesuaian Penerapan Prinsip Efektif dan Efisien Pengadaan Barang dan Jasa Konstruksi Pemerintah di Surabaya - Patrisius Valdoni Sandi; Felisitas Sintia Empak; Venansius Janto (Universitas Dr. Soetomo, 2023)
Government Procurement of Goods and Services (PBJP) of construction is one of the products of the government policy system to meet the infrastructure needs of the community so that it is necessary to implement it professionally by applying PBJP principles including efficient and effective principles. The city of Surabaya as one of the largest cities in Indonesia has massive infrastructure development and has a good record in implementing its PBJP. Therefore, this research is needed to analyze the application of the efficient and effective principles of PBJP in the construction sector in Surabaya, so that it can be an example and reference for the development of PBJP service systems in other regions in Indonesia. Using the Importance Performance Analysis (IPA) approach, the degree of conformity of the application of efficient and effective principles was obtained, which reached 87.91% and 86.31%, respectively. However, with a value that is still below 100%, it is necessary to make improvements. Based on the analysis with quadrant propagation, the indicators needed to be improved immediately with the classification of quadrant A (the main priority of improvement) were obtained to improve the suitability of the application of the effective principle of fi among which are trimming the procurement process time and trimming administrative costs. Meanwhile, to improve the conformity of efficient principles, among others, is to improve indicators of program integration, system quality, and minimize the number of face-to-face meetings in the implementation of the face-to-face system.